The Study of Morphologieal Features of Spermatozoa under Ditl'erent Temperature by Seanning Electron Microscope - Chang Kah, Haw (Universiti Sains Malaysia, 2009)
Semen is the body fluid frequently found in sexual crimes. It is principally comprised of spermatozoa suspended in seminal plasma Spermatozoa with distinct and characteristic appearance can be detected and confinned microscopically. In this study, the morphological features of spermatozoa under different temperature exposures were observed and examined by scanning electron microscope which was greatly used for the observation of discrete cell surfaces in three dimensional views at high magnification. 10 samples collected at Cytology section of Pathology Laboratory, Hospital Universiti Sains Malaysia, were divided into three different portions and kept into three different temperatures, including 55°C, 4°C and room temperature for a 5 day period. All the samples were observed by scanning electron microscope after exposure to respective temperature. Different scores were given to varied morphological features of spermatozoa observed. Through the scoring of morphological features, statistical analysis was conducted for the determination of any significant change. Result of the examination showed significant difference in the morphological features of spermatozoa for both the experimental samples as compared to the control samples. After the high temperature exposure on the samples, significant changes in the shape and surface of the bead, acrosome morphology and mid-piece of spermatozoa were found Tapered end head was seen on heat exposure. In addition, depressions and fossa were found on the surface of the head with damaged acrosome morphology. Bent mid-piece of spennatozoa was also significantly observed with high temperature exposure. On the other hand, significant changes were found with the samples on cooling. Tail and mid-piece of spermatozoa differed significantly with control samples on exposure to low temperature. Hair-pinned and severe coiled tails of spermatozoa were found in cooled samples. Mid-piece of spermatozoa was also disrupted with thinning and bending on low temperature exposure. Differences in the morphological features of spermatozoa on exposure to different temperature can be used as a tool to establish the condition of a sexual crime scene.